Oxford Research Encyclopedia of Religion 2017
DOI: 10.1093/acrefore/9780199340378.013.414
|View full text |Cite
|
Sign up to set email alerts
|

Commerce, Consumerism, and Christianity in America

Abstract: American Christianity and commerce are bound together by their mutual history. In colonial America, Puritans excelled at the skills of capitalism, and in the 19th, 20th, and 21st centuries, Christian corporations have tied together religious and corporate culture. Even when corporations and churches have maintained a distinct boundary between faith and the market, American religion and capitalism seem to be uniquely compatible. Ministers and gurus use mass media to disseminate their message (via TV, radio, boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Multiple studies have shown how the market dominates other spheres, including the religious one (most recently, the comprehensive monograph by McCarraher, 2019). The argument of this article is different as it shows that the market logic and the religious logic might not be as opposed as is often believed (Logan, 2017). From the point of view of the everyday religious practices, the two logics are often neither contradictory nor exclusive.…”
Section: Introductionmentioning
confidence: 71%
“…Multiple studies have shown how the market dominates other spheres, including the religious one (most recently, the comprehensive monograph by McCarraher, 2019). The argument of this article is different as it shows that the market logic and the religious logic might not be as opposed as is often believed (Logan, 2017). From the point of view of the everyday religious practices, the two logics are often neither contradictory nor exclusive.…”
Section: Introductionmentioning
confidence: 71%